PENDEKATAN TIGA TAHAP DALAM PERCEPATAN PEMBELAJARAN ILMU WARIS - Firdaos . (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2020)
This research is motivated by the results of preliminary research on "Second Semester Student Understanding of STAI Sebelas April Sumedang Academic Year 2016/2017 Against Inheritance Science". Two conclusion indicators were obtained, 1. understanding 37 students of inheritance science reached 23.9% very little category, and 2. Related to the difficulty of learning inheritance science reached 75.6% category mostly. This study aims to find solutions to learning problems in inheritance science material that are deemed difficult. This is evident from the results of preliminary research, the results are as illustrated above. Based on this, research that is deemed appropriate to these problems uses classroom action research (PTK). This classroom action research goes through cycle 1 meeting one and meeting two, and cycle 2 meeting one and meeting two with a Three-Stage Approach pattern, namely, the first stage discussing formulas and the composition of the male and female heirs, the second stage discussing furudulmuqaddarah (section certain), and stage three discussion of the procedure for calculating the distribution of inheritance using a descriptive qualitative approach. The research subjects were 47 fourth semester students of STAI Sebelas April Sumedang, 2018/2019 Academic Year. This study concludes by the learning process through cycle 1 and cycle 2, the average value of 96.5% is very high.